Pushing on a string: State-owned enterprises and monetary policy transmission in China - Hongyi Chen; Ran Li; Peter Tillmann (Philipps-University Marburg, School of Business and Economics, 2018)
This paper studies whether monetary transmission in China is asymmetric. While researchers found an asymmetric transmission in the U.S. and other economies, China offers a specific rationale for asymmetries: the presence of state-owned enterprises (SOEs) enjoying preferential access to financing. To study the consequences of SOEs for policy transmission, we differentiate between expansionary and restrictive policy shocks and argue that SOEs should suffer less from a policy tightening and benefit more from a policy easing. Based on sector-specific macroeconomic time series and a large firm-level data set, we provide evidence of a systematic and sizable asymmetry in the transmission of monetary policy shocks in China. The nature of the asymmetry is consistent with the notion of explicit or implicit government-guarantees of SOEs and has consequences for the adjustment of aggregate variables. In contrast to other central banks, the People's Bank of China seems to be able to "push on a string".
Keywords: E32; E44; G32; 330; monetary transmission; state-owned enterprises; financial system; VAR; state-dependent local projections; firm-level data